Comparison of the Safety and Effectiveness of Percutaneous Endoscopic Lumbar Discectomy for Treating Lumbar Disc Herniation Under Epidural Anesthesia and General Anesthesia - Zhiqiang Ren; Shenghua He; Jiao Li; Yeguang Wang; Juyi Lai; Zhitao Sun; Hualong Feng; Jian Wang (Neurospine, 2020)
Objective To assess the safety and effectiveness of percutaneous endoscopic lumbar discectomy (PELD) under epidural anesthesia (EA) and general anesthesia (GA) for treating lumbar disc herniation (LDH). Methods A retrospective study involving 86 patients with LDH managed by PELD under EA and GA was conducted from July 2018 to March 2019. These patients were divided into 2 groups according to the type of anesthesia. Patient’s demographics data as well as the operation time, complications, fluoroscopy shots, visual analog scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopaedic Association (JOA), and MacNab scores of the 2 groups were recorded. All of the patients were followed-up at 6 months after operation. Results There were no significant differences were detected in the preoperative demographics between the groups (p > 0.05). Two cases (4.8%) under GA developed transient motor weakness, 3 cases (7.4%) presented numbness of lower limb, and 1 case (2.4%) had cauda equina syndrome after operation. In EA group, 1 case (2.2%) had motor weakness and 3 cases (6.7%) had lower limb numbness, which resolved completely at the last follow-up. There was significant difference between preoperative VAS, JOA, and ODI scores and postoperative scores (p < 0.01). Moreover, there were no differences in the operation time, fluoroscopy shots, and MacNab scores between the 2 groups (p > 0.05). Conclusion EA and GA in PELD are effective and safe, and no significant difference in complications was observed. Based on our experience, we recommended junior surgeons to perform PELD under EA for getting feedback from the patient to avoid nerve injury and reduce the radiation dose. The concentration of ropivacaine in EA should be considered carefully.